The complete mitochondrial genome of Parabotia banarescui (Cypriniformes: Cobitidae). (3rd May 2016) - Wan, Quan; Wei, Min; Yu, Peng; Yang, Yingming
Abstract: Parabotia banarescui is a small-sized fish species of the family Cobitidae. In this study, we determined the complete mitochondrial genome of P. banarescui . The complete mitochondrial genome of P. banarescui was 16, 590 bp in length with the overall nucleotide base composition of A (31.00%), T (25.35%), G (16.02%) and C (27.63%), as well as an AT content of 56.35%. Besides, it contained 2 rRNA genes, 13 protein-coding genes, 22 tRNA genes, a control region and an L-strand replication origin (OL ).